2020
DOI: 10.1016/j.celrep.2020.108491
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Reprogramming by Disturbed Flow Revealed by Single-Cell RNA and Chromatin Accessibility Study

Abstract: Highlights d scRNA-seq and scATAC-seq of mouse carotid arteries after PCL surgery are presented d Carotid artery endothelial cells are heterogeneous and plastic in response to flow d Disturbed flow reprograms ECs to proatherogenic EndMT and EndICLT phenotypes d Disturbed flow regulates access to known and unreported TF binding sites

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
169
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(181 citation statements)
references
References 73 publications
(97 reference statements)
12
169
0
Order By: Relevance
“…Furthermore, both our study and the endothelial-lineage tracing study similarly demonstrated that ECs which undergo EndMT rarely give rise to vascular smooth muscle cells (VSMCs) in plaques. However, some studies showed that VSMCs or immune cells arise from EndMT in angiogenesis ( Rohlenova et al, 2020 ) or in carotid artery exposed to disturbed flow ( Andueza et al, 2020 ). Unexpectedly, we also identified the presence of EndMT-derived fibroblast-like cells in the Chow group (6.63% EndMT + of total ECs).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both our study and the endothelial-lineage tracing study similarly demonstrated that ECs which undergo EndMT rarely give rise to vascular smooth muscle cells (VSMCs) in plaques. However, some studies showed that VSMCs or immune cells arise from EndMT in angiogenesis ( Rohlenova et al, 2020 ) or in carotid artery exposed to disturbed flow ( Andueza et al, 2020 ). Unexpectedly, we also identified the presence of EndMT-derived fibroblast-like cells in the Chow group (6.63% EndMT + of total ECs).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, scRNA-seq and ATAC-sequencing (to characterize the epigenomic landscape) of ECs from mouse carotid arteries after partial ligation illustrated that disturbed flow induced reprogramming of ECs toward an immune cell-like phenotype (coined “EndICLT”), expressing macrophage markers [ 100 ]. Tissue-specific endothelial genes (enriched in the brain, heart, lungs, and kidney [ 4 ]) were expressed at low or undetectable level in carotid ECs [ 100 ], further illustrating the tissue- and vascular bed-specific EC heterogeneity. Notably, disturbed flow also induced this EndICLT phenotype in cultured human aortic ECs, in the absence of immune cells [ 100 ].…”
Section: Ec Heterogeneity In Tissue Repairmentioning
confidence: 99%
“…Tissue-specific endothelial genes (enriched in the brain, heart, lungs, and kidney [ 4 ]) were expressed at low or undetectable level in carotid ECs [ 100 ], further illustrating the tissue- and vascular bed-specific EC heterogeneity. Notably, disturbed flow also induced this EndICLT phenotype in cultured human aortic ECs, in the absence of immune cells [ 100 ]. Thus, ECs are highly plastic cells that transition to immunomodulatory cell phenotypes, identifiable by single-cell analysis as a separate subset [ 100 ].…”
Section: Ec Heterogeneity In Tissue Repairmentioning
confidence: 99%
See 2 more Smart Citations